Eine neue Oedostethus-art (Coleoptera, Elateridae, Negastriinae) aus nord des europäischen teils Russlands mit der übersicht der verwandten arten - Dolin, W.G.; Medwedew, A.A. (Вестник зоологии, 2002)
One new species of the genus Oedostethus LeConte, 1853 from North of European Territory of Russia is described and illustrated: Oe. similarius sp. n. similar to Oe. curatus Candeze, but well distinct by the different prothorax shape, longer antennae and different aedeagus form. A key for 5 related species is provided.